Tuning of the magnetostrictive properties of CoFe2O4 by Mn substitution for Co - Bhame, Shekhar D.; Joy, Pattayil Alias (Journal of Applied Physics, 2006)
Marked changes in the magnetostriction of CoFe2O4 in the substitution of Mn for Co has been observed. The magnetostriction parallel to the applied field direction decreases with increasing Mn content, whereas the magnetostriction perpendicular to the field showed a marked increase for 10% of the Mn substitution. The observed magnetostrictive properties are correlated with the magnetic properties. The results suggest the possibility of tuning the magnetostrictive properties of cobalt ferrite for various applications by proper substitution. (c) 2006 American Institute of Physics.